Structured Polyvinyl Alcohol/Zeolite/Carbon Composites Prepared Using Supercritical Fluid Extraction Techniques as Adsorbent for Bioethanol Dehydration - Joddy Arya Laksmono; Mahmud Sudibandriyo; Asep Handaya Saputra; Agus Haryono (International Journal of Chemical Engineering)
Introduction. Adsorption is a purification process with a more efficient energy level than others. Adsorption performance is strongly influenced by the ability of the adsorbent to be used; therefore, the modification of the adsorbent becomes a very important key for the purification process that occurs. Methods. In this study, the preparation of composite adsorbents was carried out by combining polyvinyl alcohol (PVA), zeolite (Zeo), and activated carbon (AC) as precursors. The crosslinking process was fulfilled by adding glutaraldehyde to the precursor mixtures followed by a supercritical fluid CO2 extraction (SFE) technique to create conditions for the crosslinking process. The composites were analyzed using Braunner–Emmet–Teller (BET) surface area analysis, Fourier-transform infrared (FTIR), differential scanning calorimetry (DSC), and scanning electron microscopy with energy dispersive X-ray (SEM/EDX-mapping), while individual and composite adsorbents were evaluated for their ability in bioethanol dehydration at various initial concentrations of ethanol and temperature. Results. The BET characterization shows that composite preparation under supercritical CO2 conditions provides reasonable surface areas, which are proportional to the content of activated carbon. The crosslinking process has been described by FTIR data interpretation, showing that PVA and glutaraldehyde were properly distributed on Zeo and AC precursors. The DSC characterization results give information that PVA successfully forms hydrophilic composites within Zeo and AC. The SEM micrograph analysis shows the formation of pores on the surface and cross section in structured adsorbents. The experimental adsorption shows that an increasing amount of AC in the composites increases the capacity of water adsorption (i.e., 0.80 gram of water/gram of adsorbent for PVA/Zeo/AC = 1 : 1 : 1 at 22°C). However, the effect is not significant when the ratio of AC is less than 0.5. As expected, the lower temperature increases the adsorption capacity. Further, by using approximately 4.5 gram adsorbents composite in 30 ml of water-ethanol mixtures, high concentration of bioethanol (>99%) can be achieved at various temperatures from 22°C to 40°C and bioethanol initial concentration from 88% to 96%. Conclusion. The SFE technique provides distinguished adsorbents composite properties. Further, the new composites provide about four times better adsorption capacity than that showed in the individual adsorbents test. The addition of AC influences on increasing the capacity and adsorption kinetics value.